2012
DOI: 10.1038/cgt.2012.53
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of zinc finger protein X-linked inhibits prostate cancer cell proliferation and induces apoptosis by activating caspase-3 and caspase-9

Abstract: Zinc finger protein X-linked (ZFX) is a highly conservative mammalian gene with related functions in cell survival and proliferation. However, there are limited reports on regulation of ZFX as a therapeutic target in cancer treatment. In this study, the expression of ZFX in prostate cancer with matched normal adjacent tissues (n ¼ 45) and benign prostatic hyperplasia (BPH) tissues (n ¼ 16) were observed by immunohistochemical analysis. The effect of lentiviral siRNA (small interference RNA)-mediated dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…In accordance with findings from previous studies (Fang et al 2012(Fang et al , 2014aJiang et al 2012a;Yang et al 2014Yang et al , 2015, we found that the top categories of genes affected by ZFX knockdown are related to the cell cycle, to the DREAM complex (which contains E2F …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with findings from previous studies (Fang et al 2012(Fang et al , 2014aJiang et al 2012a;Yang et al 2014Yang et al , 2015, we found that the top categories of genes affected by ZFX knockdown are related to the cell cycle, to the DREAM complex (which contains E2F …”
Section: Discussionsupporting
confidence: 92%
“…We chose to use these cancer models because there is a strong link in these four cancer types between ZFX expression and cell proliferation, tumor development, or patient survival. For example, prostate cancer tissues exhibit significantly higher ZFX expression than benign prostatic hyperplasia and adjacent tissues and siRNAmediated knockdown of ZFX suppresses the proliferation of prostate cancer cells and reduces the number of colonies in colony forming assays (Jiang et al 2012a). Similarly, expression of ZFX is high in advanced invasive breast cancers and knockdown of ZFX reduces the proliferation rate of breast cancer cells (Yang et al 2014).…”
Section: Zfx Binds To Cpg Island Promoter Regionsmentioning
confidence: 99%
“…Consistent with the results that ZFX knockdown caused cell cycle arrest in tongue SCC cell lines, previous studies showed that ZFX knockdown could inhibit the expression of cell cycle factors such as cyclin D1 and B1 in multiple types of cancer (18,20,21). Studies also found that ZFX depletion enhanced the expression of apoptotic factors including bax, caspase 1, 3 and 9 or inhibited the expression of anti-apoptotic factor such as bcl-2 in diverse cancers (12)(13)(14)18,20,21), which may account for the ZFX knockdown-induced cell apoptosis. Thus, it is quite possible that these mechanisms also function in tongue SCC, and further investigations are urgently needed to elucidate the mechanisms associated with ZFX-mediated tongue SCC development.…”
Section: Discussionmentioning
confidence: 99%
“…ZFX has been recognised as an oncogene in a number of cancers (reviewed in [68]). In prostate cancer cell lines, ZFX has been shown to drive cell proliferation and promote cell survival [69] and expression of ZFX has been shown to be elevated in prostate tumours [69,70]. There is no known link between the functions of ZFX and AR.…”
Section: Discussionmentioning
confidence: 99%